'Skywalker' surgical robot for total knee arthroplasty: An experimental sawbone study. Issue 5 (5th June 2021) - Xia, Runzhi; Tong, Zhicheng; Hu, Yi; Kong, Keyu; Wu, Xiulin; Li, Huiwu
Abstract: Background: Currently, robot‐assisted surgical systems are used to reduce the error range of total knee arthroplasty (TKA) osteotomy and component positioning. Methods: We used 20 sawbone models of the femur and 20 sawbone models of the tibia and fibula to evaluate the osteotomy effect of 'Skywalker' robot‐assisted TKA. Results: The maximal movement of the cutting jig was less than 0.25 mm at each osteotomy plane. The mean and standard deviation values of the angle deviation between the planned osteotomy plane and the actual osteotomy plane at each osteotomy plane were not more than 1.03° and 0.55°, respectively. The mean and standard deviation values of absolute error of resection thickness at each osteotomy position were less than 0.78 and 0.71 mm, respectively. Conclusions: The 'Skywalker' system has good osteotomy accuracy, can achieve the planned osteotomy well and is expected to assist surgeons in performing accurate TKA in clinical applications in future.